The relationship between aerobic capacity and sensitivity to pressure and ischaemic noxious stimuli - Jones, M.; Booth, J.; Taylor, J.; Barry, B. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Anecdotally endurance athletes are stoical, but there is limited evidence that tolerance of discomfort contributes to enhanced endurance. There is some evidence that aerobic exercise training reduces pain sensitivity (Anshel and Russell, 1994), however it is unclear whether enhanced tolerance of discomfort contributes to this adaptation. Studies on athletes and pain sensitivity have yielded equivocal findings (Scott and Gjisbers, 1981). Methods: Ten males (24.2 yrs; BMI 23.7; VO2peak 44.5 ml/kg/min) and 6 females (25.3 yrs; BMI 21.7; VO2peak 42.3 ml/kg/min) participated in this study. Pressure pain threshold was measured at muscular sites on the upper and lower body using an algometer. Pain tolerance was assessed using a submaximal effort tourniquet test. Participants performed repetitive hand grip exercise (30 % maximum force; 4 s grip, 4 s rest) with upper arm occlusion for as long as tolerable or a maximum of 10 min. Pain tolerance was quantified by the number of seconds subjects were willing to continue exercise under the ischemic conditions as well as by subjective rating of pain on a visual analogue scale every 30 s. A maximal aerobic test was performed on a cycle ergometer to determine the subjects level of aerobic fitness. Results: No correlation was observed between ischaemic pain tolerance and aerobic capacity for males (r-squared = 0.001, p = 0.92), females (r-squared = 0.05, p = 0.65) or for the normalised data set combining both sexes and accounting for subject age (r-squared <0.001, p = 0.99). For pressure pain, there was a significant inverse relation between normalized aerobic capacity of the male subjects and pressure pain thresholds of the upper (r-squared = 0.41, p < 0.05) and lower body (r-squared = 0.75, p < 0.05). Hence, male subjects with relatively higher aerobic capacity tended to have lower pressure pain thresholds. For female subjects, these associations were weaker and opposite (upper: 0.34, p = 0.22, lower: 0.09, p = 0.57). Discussion: Ischaemic pain tolerance, arguably the more similar to pain experienced during an endurance task, did not correlate with aerobic capacity. The inverse relation between pressure pain threshold and aerobic capacity in males possibly arose from fitter males having lower subcutaneous adiposity (Finocchietti et al., 2011), though anthropometric data in the present study do not support this. A larger sample incorporating subjects from a broader range of aerobic capacities will extend and verify these findings.